2013
DOI: 10.1111/ajt.12405
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell-Derived C3a and C5a Costimulate Human T Cell Alloimmunity

Abstract: Emerging evidence indicates that complement provides costimulatory signals for murine T cells but whether complement impacts human T cells remains unclear. We observed production of complement activation products C3a and C5a during in vitro cultures of human T cells responding to allogeneic dendritic cells (DC). Both partners expressed the receptors for C3a (C3aR) and C5a (C5aR), and C3aR- and C5aR-antagonists inhibited T cell proliferation. Recombinant C3a/C5a promoted CD4+ T cell expansion, bypassed the inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 38 publications
3
102
3
Order By: Relevance
“…Taken together, our data strongly argue against C5aR1 expression in naive and activated murine CD4 + T cells. This finding is in contrast to results observed in the human system, in which C5aR1 expression was demonstrated in T cells (76). Based on our findings, we suggest a model by which C5a regulates CD4 + T cell responses in the mouse exclusively at the APC level.…”
Section: Cd11bcontrasting
confidence: 99%
“…Taken together, our data strongly argue against C5aR1 expression in naive and activated murine CD4 + T cells. This finding is in contrast to results observed in the human system, in which C5aR1 expression was demonstrated in T cells (76). Based on our findings, we suggest a model by which C5a regulates CD4 + T cell responses in the mouse exclusively at the APC level.…”
Section: Cd11bcontrasting
confidence: 99%
“…Confirmatory human experiments published in 2013 show that C3a and C5a are generated during in vitro cultures of human T cells responding to allogeneic dendritic cells (DCs) (27). Both partners express the receptors for C3a and C5a (124)(125)(126)(127), and C3aR-and C5aR-antagonists inhibit human T-cell proliferation, whereas recombinant C3a/C5a promotes alloreactive human CD4 1 T-cell expansion.…”
Section: Complement and T Cell-mediated Transplant Rejectionmentioning
confidence: 96%
“…C3aR/ C5aR signaling is also required for T-cell homeostasis, because T cells deficient in both receptors spontaneously undergo accelerated cell death in vitro and in vivo (24). The observations derived from murine models also apply to human T cells (27). Building on these findings, a 2013 publication showed that resting human CD4 1 T cells contain C3 in granules that is rapidly cleaved by cathepsin-L to C3a and secreted after CD3 ligation.…”
Section: Links Between Complement and Adaptive Immunitymentioning
confidence: 99%
“…Complement has been considered more recently to be involved in both the homeostasis and the effector functions of the T cell. In cognate T cell and APC interactions the locally produced C3a and C5a are able to bind to their respective receptor on the T cell membrane, which subsequently stimulates the effector functions and maintains the viability of the T cell [100]. The T cell itself can produce complement components upon activation via T cell receptor (TCR) and CD28, which results in induced protein expression of C3, C5, FB and FD [101][102][103][104].…”
Section: T Cellsmentioning
confidence: 99%